IT ROARS BUT THEN IT SUFFERS: AMERICA IN THE INTERBELLUM AS DEPICTED IN THE GREAT GATSBY - Mualim, Maulana; Khristianto, Khristianto; Thabib Kariadi, Mustasyfa (Universitas Negeri Yogyakarta, 2023)
Francis Scott Fitzgerald’s The Great Gatsby that is written in 1925 records one of the most remarkable decades in American history. American economy “roars” in the interbellum/interwar period with the advancement of technology and the stock market but then it declined by excessive consumerism. This article seeks to identify the changes in the American economy and consumer culture as depicted in Fitzgerald’s The Great Gatsby and the subsequent depression that happened. A new historicism technique is applied to describe some major factors enabling America in the twenties to lead the world’s economy as depicted in the novel and factors ending the development. By using a content analysis technique, data in the form of excerpts from the novel are collected. The data are then analyzed following the thematic analysis principles. The result of the study points out some changes that made America in the twenties roar are the increase of middle-class people, the widespread use of technology, the development of the stock market, the affordability of automobiles, and the freedom to speak and act. The glorious decades came to an end after 1939 when the stock market crashed, consumerism escalated, credit card use expanded and banks got a “panic attack”. The implication for today’s lifestyle is mentioned.